PENERAPAN PENDEKATAN KONSTRUKTIVISME DENGAN MODEL DISCOVERY LEARNING DALAM UPAYA PENINGKATAN KEMAMPUAN PENALARAN DAN HUBUNGAN MOTIVASI BELAJAR MATEMATIKA SISWA - Wawan Hernawan; Ricky Yuliardi; Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Implementation Approach Constructivism Model Discovery Learning In Improving Reasoning Ability And Relationships Motivation Math Student. The background of this study is to improve the students mathematical reasoning skills by using the discovery learning models and relationships motivation math student.The result of the initial test indicates that the average value of control class is 10,99 and the average value of experimental class is 10,95. Meanwhile the result of the final test shows that the average value of control class is 15,27 and the average value of experimental class is 21.63 Based on the outcome of the initial and final data analysis, it can be concluded that mathematical learning applying by the discovery learning models is better than direct instructional. However, the increase of experimental students skills of mathematical reasoning is medium level. In addition, from the results of Spearman correlation test is known that there is a relationship between learning motivation and mathematical reasoning abilities of students. While the results of student questionnaire responses, it is known that the students showed a positive response to discovery learning models